2008
DOI: 10.1007/s11237-008-9028-7
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the surface layer and catalytic activity of Ta2O5 with Pt or Pd additives in the oxidation of hydrogen

Abstract: The catalytic activity in the oxidation of hydrogen (in the gaseous state in the presence of excess oxygen) has been studied for samples of Pt(Pd)/Ta 2 O 5-x , formed by reduction with hydrogen. The samples obtained had greater activity than the traditional catalysts Pt(Pd)/Al 2 O 3 . According to X-ray diffraction analysis and electron microscopic studies, Ta 2 O 5-x becomes amorphous with the formation of more reduced non-stoichiometric oxygen-deficient tantalum oxides with a surface layer of catalyst.It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Surface Ru serves as a source of active oxygen and thus enhances CO oxidation, 10 but TaO y diminishes the adsorption of CO, possibly through a decrease in the Pt-CO bond strength. The Ta oxidation state was not characterized in the materials of Ueda et al, 9 but Lesnyak et al 11 found that the use of a similar material as a gas phase H 2 oxidation catalyst resulted in partial reduction of the Ta 2 O 5 support. The electrode, consisting of Pt nanoparticles on a Ta 2 O 5 support, was characterized by XRD, electron diffraction and X-ray spectral microanalysis both before and after use as a catalyst for oxidation of H 2 in a fuel stream with 20:1 O 2 :H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Surface Ru serves as a source of active oxygen and thus enhances CO oxidation, 10 but TaO y diminishes the adsorption of CO, possibly through a decrease in the Pt-CO bond strength. The Ta oxidation state was not characterized in the materials of Ueda et al, 9 but Lesnyak et al 11 found that the use of a similar material as a gas phase H 2 oxidation catalyst resulted in partial reduction of the Ta 2 O 5 support. The electrode, consisting of Pt nanoparticles on a Ta 2 O 5 support, was characterized by XRD, electron diffraction and X-ray spectral microanalysis both before and after use as a catalyst for oxidation of H 2 in a fuel stream with 20:1 O 2 :H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, both theories fail to explain the lack of response to CO molecules in dense-gate devices or the reversibility of the CO effects on the devices in pure nitrogen atmospheres. The CO spillover phenomenon (interphase diffusion of adsorbed atoms or molecules), which is common metal-assisted catalysis on mixed oxides [15][16][17], could provide a more consistent explanation. According to this, the sensor's response to CO could be attributed to CO molecules that, after being adsorbed at the Pt near the bare patches of TaO x , migrate to this oxide via spillover [3,18].…”
Section: Fig 3 Dynamic Response Of a Pt/taox/sio2/sic Mis Capacitor mentioning
confidence: 99%
“…Prior work had reported TaO x carburization temperatures above 1200 °C; [13,14] however, we hypothesize that Pt facilitates the TaO x reduction via H 2 spillover and decomposition of CH 4 , which serves as the carbon source, thereby substantially decreasing the carburization temperature. [15][16][17][18] Pt/TaC nanoparticles supported on carbon were subsequently obtained by dissolving the silica shell using ethanol-diluted hydrofluoric acid solution and then dispersing the particles onto a carbon black support. Pt/TaC nanoparticles with four different shell thicknesses were prepared by using different amounts of Pt precursors.…”
Section: Synthesis and Characterization Of Pt/tac Nanoparticlesmentioning
confidence: 99%